A protecting group-free synthesis of the Colorado potato beetle pheromone - Wu, Zhongtao; Jäger, Manuel; Buter, Jeffrey; Minnaard, Adriaan J. (Beilstein Journal of Organic Chemistry, 2013)
A novel synthesis of the aggregation pheromone of the Colorado potato beetle, Leptinotarsa decemlineata, has been developed based on a Sharpless asymmetric epoxidation in combination with a chemoselective alcohol oxidation using catalytic [(neocuproine)PdOAc]2OTf2. Employing this approach, the pheromone was synthesized in 3 steps, 80% yield and 86% ee from geraniol.
Keywords: aggregation pheromone; catalysis; Colorado potato beetle; Leptinotarsa decemlineata; oxidation; natural product

(untitled) - Kuhar, T. P.; Mori, K.; Dickens, J. C. (Agr. Forest Entomol., 2006)

(untitled) - Roush, R. T.; Hoy, C. W.; Ferro, D. N.; Tingey, W. M. (J. Econ. Entomol., 1990)

(untitled) - Ioannidis, P. M.; Grafius, E.; Whalon, M. E. (J. Econ. Entomol., 1991)

(untitled) - Grafius, E. (J. Econ. Entomol., 1997)

(untitled) - Połeć, I. (Pestycydy/Pesticides, 2010)

(untitled) - Olson, E. R.; Dively, G. P.; Nelson, J. O. (J. Econ. Entomol., 2000)

(untitled) - Dickens, J. C.; Oliver, J. E.; Hollister, B.; Davis, J. C.; Klun, J. A. (J. Exp. Biol., 2002)

(untitled) - Oliver, J. E.; Dickens, J. C.; Glass, T. E. (Tetrahedron Lett., 2002)

(untitled) - Tashiro, T.; Mori, K. (Tetrahedron: Asymmetry, 2005)

(untitled) - Babu, B. N.; Chauhan, K. R. (Tetrahedron Lett., 2009)

(untitled) - Faraldos, J. A.; Coates, R. M.; Giner, J.-L. (J. Org. Chem., 2013)

(untitled) - Painter, R. M.; Pearson, D. M.; Waymouth, R. M. (Angew. Chem., Int. Ed., 2010)

(untitled) - Chung, K.; Banik, S. M.; De Crisci, A. G.; Pearson, D. M.; Blake, T. R.; Olsson, J. V.; Ingram, A. J.; Zare, R. N.; Waymouth, R. M. (J. Am. Chem. Soc., 2013)

(untitled) - Jäger, M.; Hartmann, M.; de Vries, J. G.; Minnaard, A. J. (Angew. Chem., Int. Ed., 2013)

(untitled) - Conley, N. R.; Labios, L. A.; Pearson, D. M.; McCrory, C. C. L.; Waymouth, R. M. (Organometallics, 2007)

(untitled) - Hashimoto, M.; Harigaya, H.; Yanagiya, M.; Shirahama, H. (J. Org. Chem., 1991)

(untitled) - Katsuki, T.; Sharpless, K. B. (J. Am. Chem. Soc., 1980)

(untitled) - Gao, Y.; Hanson, R. M.; Klunder, J. M.; Ko, S. Y.; Masamune, H.; Sharpless, K. B. (J. Am. Chem. Soc., 1987)

(untitled) - Nacro, K.; Baltas, M.; Escudier, J.-M.; Gorrichon, L. (Tetrahedron, 1996)

(untitled) - Molawi, K.; Delpont, N.; Echavarren, A. M. (Angew. Chem., Int. Ed., 2010)

(untitled) - Mohapatra, D. K.; Pramanik, C.; Chorghade, M. S.; Gurjar, M. K. (Eur. J. Org. Chem., 2007)

(untitled) - González, I. C.; Forsyth, C. J. (J. Am. Chem. Soc., 2000)

(untitled) - Hanson, R. M. (Tetrahedron Lett., 1984)

(untitled) - Corey, E. J.; Ha, D.-C. (Tetrahedron Lett., 1988)

(untitled) - Kolb, M.; Van Hijfte, L.; Ireland, R. E. (Tetrahedron Lett., 1988)

(untitled) - Marshall, J. A.; Trometer, J. D.; Cleary, D. G. (Tetrahedron, 1989)

(untitled) - Van Hijfte, L.; Kolb, M. (Tetrahedron, 1992)

(untitled) - Ray, N. C.; Raveendranath, P. C.; Spencer, T. A. (Tetrahedron, 1992)

(untitled) - Mori, N.; Kuwahara, Y.; Kurosa, K. (Bioorg. Med. Chem., 1996)

(untitled) - Underwood, B. S.; Tanuwidjaja, J.; Ng, S.-S.; Jamison, T. F. (Tetrahedron, 2013)